Automatic Classification of Neuromuscular Diseases in Children Using Photoacoustic Imaging - Schlereth, Maja; Stromer, Daniel; Breininger, Katharina; Wagner, Alexandra; Tan, Lina; Maier, Andreas; Knieling, Ferdinand (Informatik aktuell, 2022)
Neuromuscular diseases (NMDs) cause a significant burden for both healthcare systems and society. They can lead to severe progressive muscle weakness, muscle degeneration, contracture, deformity and progressive disability. The NMDs evaluated in this study often manifest in early childhood. As subtypes of disease, e.g. Duchenne muscular dystropy (DMD) and spinal muscular atrophy (SMA), are difficult to differentiate at the beginning and worsen quickly, fast and reliable differential diagnosis is crucial. Photoacoustic and ultrasound imaging has shown great potential to visualize and quantify the extent of different diseases. The addition of automatic classification of such image data could further improve standard diagnostic procedures.We compare deep learning-based 2-class and 3-class classifiers based on VGG16 for differentiating healthy from diseased muscular tissue. This work shows promising results with high accuracies above 0.86 for the 3-class problem and can be used as a proof of concept for future approaches for earlier diagnosis and therapeutic monitoring of NMDs.<br
CRIS-Team Scopus Importer:2022-05-06

Continuous monitoring of SARS-CoV-2 seroprevalence in children using residual blood samples from routine clinical chemistry - Wachter, Felix; Regensburger, Adrian; Peter, Antonia Sophia; Knieling, Ferdinand; Wagner, Alexandra; Simon, David; Hörning, André; Wölfle, Joachim; Überla, Klaus; Neubert, Antje; Rauh, Manfred (Clinical Chemistry and Laboratory Medicine, 2022)
Objectives The assessment of SARS-CoV-2 infections in children is still challenging, but essential for appropriate political decisions. The aim of this study was to investigate whether residual blood samples can be used for SARS-CoV-2 seroprevalence monitoring in pediatrics. Methods In this repeated cross-sectional cohort study, anonymous residual blood samples from pediatric patients aged 0-17 years were collected in three time-periods (Oct.-Nov. 2020, April 2021, and June-July 2021) and analyzed for SARS-CoV-2 Spike protein (anti-S) and nucleocapsid (anti-N) antibodies using commercial antibody assays. 28 reactive samples were used to compare antibody levels with a pseudotyped neutralization assay. The results were further compared to the official national COVID-19 surveillance data to calculate the number of unreported cases. Results In total, n=2,626 individual blood samples were analyzed. In this unvaccinated pediatric cohort anti-S and anti-N antibody seroprevalence increased over the three time periods (anti-S: 1.38-9.16%, and 14.59%; anti-N: 1.26%, to 6.19%, and 8.56%). Compared to the national surveillance data this leads to a 3.93-5.66-fold increase in the number of unreported cases. However, a correlation between the cumulative incidence of the individual provinces and our assigned data was found (r=0.74, p=0.0151). In addition, reactive samples with anti-S and anti-N and samples with only anti-S showed neutralization capabilities (11/14 and 8/14, respectively). Anti-S levels were not significantly different between age groups and sexes (all p>0.05). Conclusions The present study suggests that residual blood samples from routine laboratory chemistry could be included in the estimation of the total SARS-CoV-2 seroprevalence in children.
CRIS-Team WoS Importer:2022-03-11
Keywords: COVID-19; pediatrics; prevalence; SARS-CoV-2

Contrast-Enhanced Multispectral Optoacoustic Tomography for Functional Assessment of the Gastrointestinal Tract - Paulus, Lars-Philip; Bühler, Adrian; Wagner, Alexandra; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Rother, Ulrich; Eckstein, Markus; Lang, Werner; Hörning, André; et al. (Advanced Science, 2023)
Real-time imaging and functional assessment of the intestinal tract and its transit pose a significant challenge to conventional clinical diagnostic methods. Multispectral optoacoustic tomography (MSOT), a molecular-sensitive imaging technology, offers the potential to visualize endogenous and exogenous chromophores in deep tissue. Herein, a novel approach using the orally administered clinical-approved fluorescent dye indocyanine green (ICG) for bedside, non-ionizing evaluation of gastrointestinal passage is presented. The authors are able to show the detectability and stability of ICG in phantom experiments. Furthermore, ten healthy subjects underwent MSOT imaging at multiple time points over eight hours after ingestion of a standardized meal with and without ICG. ICG signals can be visualized and quantified in different intestinal segments, while its excretion is confirmed by fluorescent imaging of stool samples. These findings indicate that contrast-enhanced MSOT (CE-MSOT) provides a translatable real-time imaging approach for functional assessment of the gastrointestinal tract.
CRIS-Team Scopus Importer:2023-06-30
Keywords: indocyanine green; intestine; multispectral optoacoustic tomography; optoacoustics; photoacoustics

High-resolution label-free mapping of murine kidney vasculature by raster-scanning optoacoustic mesoscopy: an ex vivo study - Goebel, Colin A.; Brown, Emma; Fahlbusch, Fabian; Wagner, Alexandra; Buehler, Adrian; Raupach, Thomas; Hohmann, Martin; Späth, Moritz; Burton, Neal; Wölfle, Joachim; Schmidt, Michael; Hartner, Andrea; et al. (Molecular and Cellular Pediatrics, 2022)
Background: Chronic kidney disease (CKD) is a global burden affecting both children and adults. Novel imaging modalities hold great promise to visualize and quantify structural, functional, and molecular organ damage. The aim of the study was to visualize and quantify murine renal vasculature using label-free raster scanning optoacoustic mesoscopy (RSOM) in explanted organs from mice with renal injury. Material and methods: For the experiments, freshly bisected kidneys of alpha 8 integrin knock-out (KO) and wildtype mice (WT) were used. A total of n=7 female (n=4 KO, n=3 WT) and n=6 male animals (n=2 KO, n=4 WT) aged 6 weeks were examined with RSOM optoacoustic imaging systems (RSOM Explorer P50 at SWL 532nm and/or ms-P50 imaging system at 532 nm, 555 nm, 579 nm, and 606 nm). Images were reconstructed using a dedicated software, analyzed for size and vascular area and compared to standard histologic sections. Results: RSOM enabled mapping of murine kidney size and vascular area, revealing differences between kidney sizes of male (m) and female (f) mice (merged frequencies (MF) f vs. m: 52.42±6.24 mm2 vs. 69.18±15.96 mm2, p=0.0156) and absolute vascular area (MF f vs. m: 35.67±4.22 mm2 vs. 49.07±13.48 mm2, p=0.0036). Without respect to sex, the absolute kidney area was found to be smaller in knock-out (KO) than in wildtype (WT) mice (WT vs. KO: MF: p=0.0255) and showed a similar trend for the relative vessel area (WT vs. KO: MF p=0.0031). Also the absolute vessel areas of KO compared to WT were found significantly different (MF p=0.0089). A significant decrease in absolute vessel area was found in KO compared to WT male mice (MF WT vs. KO: 54.37±9.35 mm2 vs. 34.93±13.82 mm2, p=0.0232). In addition, multispectral RSOM allowed visualization of oxygenated and deoxygenated parenchymal regions by spectral unmixing. Conclusion: This study demonstrates the capability of RSOM for label-free visualization of differences in vascular morphology in ex vivo murine renal tissue at high resolution. Due to its scalability optoacoustic imaging provides an emerging modality with potential for further preclinical and clinical imaging applications.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Chronic kidney disease; Ex vivo kidney imaging; msRSOM; Optoacoustic; Photoacoustic; Raster scanning optoacoustic mesoscopy; RSOM

Hybrid reflected-ultrasound computed tomography versus B-mode-ultrasound for muscle scoring in spinal muscular atrophy - Danko, Vera; Jüngert, Jörg M.; Schüssler, Stephanie; Bühler, Adrian; Klett, Daniel; Federle, Anna; Roos, Andreas; Lochmüller, Hanns; Neurath, Markus; Wölfle, Joachim; Trollmann, Regina; Waldner, Maximilian; et al. (Journal of Neuroimaging, 2023)
Background and Purpose: Novel light- and sound-based technologies like multispectral optoacoustic tomography (MSOT) with co-registered reflected-ultrasound computed tomography (RUCT) could add additional value to conventional ultrasound (US) for disease phenotyping in pediatric spinal muscular atrophy (SMA). The aim of this study was to investigate the quality of RUCT compared to US for qualitative and quantitative assessment of imaging neuromuscular disorders. Methods: Subanalyzing the MSOT SMA study, 288 RUCT and 276 US images from 10 SMA patients (mean age 9.0 ± 3.7) and 10 gender- and age-matched healthy volunteers (HV; mean age 8.7 ± 4.3) were analyzed for quantitative (grayscale levels [GSLs]) and qualitative (echogenicity, distribution pattern, Heckmatt scale, and muscle texture) muscle changes. RUCT and US measures were further correlated with clinical standard motor outcomes. Results: Quantitative agreement using GSLs revealed significantly higher GSLs in muscles of SMA patients compared to healthy muscles in both techniques (US mean GSL [SD] SMA vs. HV: 110.70 [27.8] vs. 68.85 [19.2], p <.0001; RUCT mean GSL [SD] SMA vs. HV: 91.81 [21.8] vs. 59.86 [8.2], p <.0001) with good correlation with motor outcome tests, respectively. Qualitative agreement between methods for muscle composition was excellent for differentiation of pathological versus healthy muscles, echogenicity, and distribution pattern, moderate for Heckmatt scale, and poor for muscle texture. Conclusions: The data suggest that RUCT may allow the assessment of basic qualitative and quantitative measures for muscular diseases with comparable results to conventional US.
CRIS-Team Scopus Importer:2023-01-20
Keywords: neuromuscular disorders; optoacoustics; photoacoustics; spinal muscular atrophy; ultrasound

Hybrid ultrasound and single wavelength optoacoustic imaging reveals muscle degeneration in peripheral artery disease - Träger, Anna P.; Günther, Josefine; Raming, Roman; Paulus, Lars-Philip; Lang, Werner; Meyer, Alexander; Kempf, Julius; Caranovic, Milenko; Li, Yi; Wagner, Alexandra; Tan, Lina; Danko, Vera; et al. (Photoacoustics, 2024)
Peripheral arterial disease (PAD) leads to chronic vascular occlusion and results in end organ damage in critically perfused limbs. There are currently no clinical methods available to determine the muscular damage induced by chronic mal-perfusion. This monocentric prospective cross-sectional study investigated n = 193 adults, healthy to severe PAD, in order to quantify the degree of calf muscle degeneration caused by PAD using a non-invasive hybrid ultrasound and single wavelength optoacoustic imaging (US/SWL-OAI) approach. While US provides morphologic information, SWL-OAI visualizes the absorption of pulsed laser light and the resulting sound waves from molecules undergoing thermoelastic expansion. US/SWL-OAI was compared to multispectral data, clinical disease severity, angiographic findings, phantom experiments, and histological examinations from calf muscle biopsies. We were able to show that synergistic use of US/SWL-OAI is most likely to map clinical degeneration of the muscle and progressive PAD.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Muscle degeneration; Muscle imaging; Optoacoustics; Peripheral artery disease; Photoacoustics

Multispectral optoacoustic tomography enables assessment of disease activity in paediatric inflammatory bowel disease - Regensburger, Adrian; Eckstein, Markus; Wetzl, Matthias; Raming, Roman; Paulus, Lars-Philip; Bühler, Adrian; Nedoschill, Emmanuel; Danko, Vera; Jüngert, Jörg; Wagner, Alexandra; Schnell, Alexander; Rückel, Aline; et al. (Photoacoustics, 2024)
Multispectral optoacoustic tomography (MSOT) allows non-invasive molecular disease activity assessment in adults with inflammatory bowel disease (IBD). In this prospective pilot-study, we investigated, whether increased levels of MSOT haemoglobin parameters corresponded to inflammatory activity in paediatric IBD patients, too. 23 children with suspected IBD underwent MSOT of the terminal ileum and sigmoid colon with standard validation (e.g. endoscopy). In Crohn‘s disease (CD) and ulcerative colitis (UC) patients with endoscopically confirmed disease activity, MSOT total haemoglobin (HbT) signals were increased in the terminal ileum of CD (72.1 ± 13.0 a.u. vs. 32.9 ± 15.4 a.u., p = 0.0049) and in the sigmoid colon of UC patients (62.9 ± 13.8 a.u. vs. 35.1 ± 16.3 a.u., p = 0.0311) as compared to controls, respectively. Furthermore, MSOT haemoglobin parameters correlated well with standard disease activity assessment (e.g. SES-CD and MSOT HbT (rs =0.69, p = 0.0075). Summarizing, MSOT is a novel technology for non-invasive molecular disease activity assessment in paediatric patients with inflammatory bowel disease.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Multispectral optoacoustic tomography; Optoacoustic imaging; Paediatric inflammatory bowel disease

Multispectral optoacoustic tomography for non-invasive disease phenotyping in pediatric spinal muscular atrophy patients - Regensburger, Adrian; Wagner, Alexandra; Danko, Vera; Jüngert, Jörg M.; Federle, Anna; Klett, Daniel; Schüssler, Stephanie; Buehler, Adrian; Neurath, Markus; Roos, Andreas; Lochmüller, Hanns; Wölfle, Joachim; et al. (Photoacoustics, 2022)
Proximal spinal muscular atrophy (SMA) is a rare progressive, life limiting genetic motor neuron disease. While promising causal therapies are available, meaningful prognostic biomarkers for therapeutic monitoring are missing. We demonstrate handheld Multispectral Optoacoustic Tomography (MSOT) as a novel non-invasive imaging approach to visualize and quantify muscle wasting in pediatric SMA. While MSOT signals were distributed homogeneously in muscles of healthy volunteers (HVs), SMA patients showed moth-eaten optoacoustic signal patterns. Further signal quantification revealed greatest differences between groups at the isosbestic point for hemoglobin (SWL 800 nm). The SWL 800 nm signal intensities further correlated with clinical phenotype tested by standard motor outcome measures. Therefore, handheld MSOT could enable non-invasive assessment of disease burden in SMA patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Multispectral optoacoustic tomography; Optoacoustics; Photoacoustics; Spinal muscular atrophie

Multispectral optoacoustic tomography of the human intestine – temporal precision and the influence of postprandial gastrointestinal blood flow - Paulus, Lars-Philip; Wagner, Alexandra; Buehler, Adrian; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Günther, Josefine; Rother, Ulrich; Lang, Werner; Hörning, André; et al. (Photoacoustics, 2023)
Multispectral optoacoustic tomography (MSOT) holds great promise as a non-invasive diagnostic tool for inflammatory bowel diseases. Yet, reliability and the impact of physiological processes during fasting and after food intake on optoacoustic signals have not been studied. In the present investigator initiated trial (NCT05160077) the intestines of ten healthy subjects were examined by MSOT at eight timepoints on two days, one fasting and one after food intake. While within-timepoint and within-day reproducibility were good for single wavelength 800 nm and total hemoglobin (ICC 0.722–0.956), between-day reproducibility was inferior (ICC −0.137 to 0.438). However, temporal variability was smaller than variation between individuals (coefficients of variation 8.9%−33.7% vs. 17.0%−48.5%). After food intake and consecutive increased intestinal circulation, indicated by reduced resistance index of simultaneous Doppler ultrasound, optoacoustic signals did not alter significantly. In summary, this study demonstrates high reliability and temporal stability of MSOT for imaging the human intestine during fasting and after food intake.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Gut; Inflammatory bowel disease; Intestinal blood flow; Multispectral optoacoustic imaging; Optoacoustic; Photoacoustic; Postprandial; Reliability; Reproducibility

NON-INVASIVE IN VIVO METABOLIC PROFILING OF INFLAMMATION IN JOINTS AND ENTHESES BY OPTOACOUSTIC IMAGING - Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Bayat, Sara; Heidemann, Robert; Steiger, F.; Krönke, Gerhard; Bohr, D.; Ramming, Andreas; Hartmann, F.; Klett, Daniel; Federle, Anna; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Non-invasive metabolic profiling of inflammation in joints and entheses by multispectral optoacoustic tomography - Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Bayat, Sara; Heidemann, Robert; Steiger, Florian; Krönke, Gerhard; Bohr, Daniela; Ramming, Andreas; Hartmann, Fabian; Klett, Daniel; Federle, Anna; et al. (Rheumatology, 2022)
Objective To explore the metabolic characteristics of arthritis and enthesitis using multispectral opto-acoustic tomography (MSOT), a technology using near-infrared multispectral laser to stimulate tissues and detect the emitted acoustic energy, enabling non-invasive quantification of tissue components in vivo based on differential absorbance at multiple wavelengths. Methods We performed a cross-sectional study in patients with RA or PsA and healthy controls (HCs). Participants underwent clinical, ultrasonographic and MSOT examination of MCP and wrist joints as well as the entheses of the common extensor tendon at the lateral humeral epicondyles and of the patellar, quadriceps and Achilles tendon. MSOT-measured haemoglobin (Hb), oxygen saturation, collagen and lipid levels were quantified and scaled mean differences between affected and unaffected joints and entheses were calculated as defined by clinical examination or ultrasonography using linear mixed effects models. Results We obtained 1535 MSOT and 982 ultrasonography scans from 87 participants (34 PsA, 17 RA, 36 HCs). Entheseal tenderness was not associated with significant metabolic changes, whereas enthesitis-related sonographic changes were associated with increased total Hb, oxygen saturation and collagen content. In contrast, the presence of arthritis-related clinical and sonographic findings showed increased Hb levels, reduced oxygen saturation and reduced collagen content. Synovial hypertrophy was associated with increased lipid content in the joints. Conclusion MSOT allows determination of distinct metabolic differences between arthritis and enthesitis in a non-invasive setting in humans in vivo.
CRIS-Team WoS Importer:2022-07-22

Non-invasive optoacoustic imaging of glycogen-storage and muscle degeneration in late-onset Pompe disease. - Tan, Lina; Zschüntzsch, Jana; Meyer, Stefanie; Stobbe, Alica; Bruex, Hannah; Regensburger, Adrian; Claßen, Merle; Alves, Frauke; Jüngert, Jörg; Rother, Ulrich; Li, Yi; Danko, Vera; et al. (Nature Communications, 2024)
Pompe disease (PD) is a rare autosomal recessive glycogen storage disorder that causes proximal muscle weakness and loss of respiratory function. While enzyme replacement therapy (ERT) is the only effective treatment, biomarkers for disease monitoring are scarce. Following ex vivo biomarker validation in phantom studies, we apply multispectral optoacoustic tomography (MSOT), a laser- and ultrasound-based non-invasive imaging approach, in a clinical trial (NCT05083806) to image the biceps muscles of 10 late-onset PD (LOPD) patients and 10 matched healthy controls. MSOT is compared with muscle magnetic resonance imaging (MRI), ultrasound, spirometry, muscle testing and quality of life scores. Next, results are validated in an independent LOPD patient cohort from a second clinical site. Our study demonstrates that MSOT enables imaging of subcellular disease pathology with increases in glycogen/water, collagen and lipid signals, providing higher sensitivity in detecting muscle degeneration than current methods. This translational approach suggests implementation in the complex care of these rare disease patients.
EVALuna2:571098

Pediatric Buried Bumper Syndrome: Diagnostic Validity of Transabdominal Ultrasound and Artificial Intelligence - Aguilar, Caroline; Regensburger, Adrian; Knieling, Ferdinand; Wagner, Alexandra; Siebenlist, Gregor; Wölfle, Joachim; Koehler, Henrik; Hörning, André; Jüngert, Jörg M. (Ultraschall in der Medizin, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-06-04

Pulmonary Dysfunction after Pediatric COVID-19 - Heiß, Rafael; Tan, Lina; Schmidt, Sandy; Regensburger, Adrian; Ewert, Franziska; Mammadova, Dilbar; Bühler, Adrian; Vogel-Claussen, Jens; Voskrebenzev, Andreas; Rauh, Manfred; Rompel, Oliver; Nagel, Armin Michael; et al. (Radiology, 2022)
Background Long COVID occurs in lower frequency in children and adolescents than in adults. Morphologic and free-breathing phase-resolved functional low-field MRI may identify persistent pulmonary manifestations after SARS-CoV-2 infection. Purpose To characterize both morphologic and functional changes of lung parenchyma on low-field MRI in children and adolescents with post COVID-19 compared with healthy controls. Materials and Methods Between August and December 2021, a cross-sectional, prospective clinical trial using low-field MRI was performed in children and adolescents from a single academic medical center. The primary outcome was the frequency of morphologic changes on MRI. Secondary outcomes included MRI-derived functional proton ventilation and perfusion parameters. Clinical symptoms, the duration from positive RT-PCR test and serological parameters were compared with imaging results. Nonparametric tests for pairwise and corrected tests for groupwise comparisons were applied to assess differences in healthy controls, recovered participants and with long COVID. Results A total of 54 participants post COVID-19 infection (mean age, 11 years ±3 [SD], 56 males) and 9 healthy controls (mean age, 10 years ±3 [SD], 70 males) were included: 29 (54%) in the COVID-19 group had recovered from infection and 25 (46%) were classified as having long COVID on the day of enrollment. Morphologic abnormality was identified in one recovered participant. Both ventilated and perfused lung parenchyma (V/Q match) was reduced from 81±6.1% in healthy controls to 62±19% (P =.006) in the recovered group and 60±20% (P=.003) in the long COVID group. V/Q match was lower in post COVID patients with infection less than 180 days (63±20%, P=.03), 180 to 360 days (63±18%, P=0.03) and 360 days ago (41±12%, P<.001) as compared with the never-infected healthy controls (81±6.1%). Conclusion Low-field MRI showed persistent pulmonary dysfunction in both children and adolescents recovered from COVID-19 and with long COVI

Shedding light on pediatric diseases: multispectral optoacoustic tomography at the doorway to clinical applications. - Regensburger, Adrian; Wagner, Alexandra; Claussen, Jing; Waldner, Maximilian; Knieling, Ferdinand (Molecular and Cellular Pediatrics, 2020)
Optoacoustic imaging (OAI), or photoacoustic imaging (PAI), has fundamentally influenced basic science by providing high-resolution visualization of biological mechanisms. With the introduction of multispectral optoacoustic tomography (MSOT), these technologies have now moved closer to clinical applications. MSOT utilizes short-pulsed near-infrared laser light to induce thermoelastic expansion in targeted tissues. This results in acoustic pressure waves, which are used to resolve specific endo- and exogenous chromophores. Especially in the pediatric population, this non-invasive imaging approach might hold fundamental advantages compared to conventional cross-sectional imaging modalities. As this technology allows the visualization of quantitative molecular tissue composition at high spatial resolution non-invasively in sufficient penetration depth, it paves the way to personalized medicine in pediatric diseases.
EVALuna2:383218

Targeting Muscular Hemoglobin Content for Classification of Peripheral Arterial Disease by Noninvasive Multispectral Optoacoustic Tomography - Günther, Josefine; Knieling, Ferdinand; Träger, Anna P.; Lang, Werner; Meyer, Alexander; Regensburger, Adrian; Wagner, Alexandra; Trollmann, Regina; Wölfle, Joachim; Klett, Daniel; Uter, Wolfgang; Uder, Michael; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2023)
Created from Fastlane, Scopus look-up

Transfontanellar Contrast-enhanced US for Intraoperative Imaging of Cerebral Perfusion during Neonatal Arterial Switch Operation - Knieling, Ferdinand; Cesnjevar, Robert; Regensburger, Adrian; Wagner, Alexandra; Purbojo, Ariawan; Dittrich, Sven; Münch, Frank; Neubert, Antje; Wölfle, Joachim; Jüngert, Jörg M.; Rüffer, André (Radiology, 2022)
Background Brain injury and subsequent neurodevelopmental disorders are major determinants for later-life outcomes in neonates with transposition of the great arteries (TGA). Purpose To quantitatively assess cerebral perfusion in neonates with TGA undergoing arterial switch operation (ASO) using transfontanellar contrast-enhanced US (T-CEUS). Materials and Methods In a prospective single-center cross-sectional diagnostic study, neonates with TGA scheduled for ASO were recruited from February 2018 to February 2020. Measurements were performed at five time points before, during, and after surgery (T1-T5), and 11 perfusion parameters were derived per cerebral hemisphere. Neonate clinical characteristics, heart rate, mean arterial pressure, central venous pressure, near-infrared spectroscopy, blood gas analyses, ventilation time, time spent in the pediatric intensive care unit, and time in hospital were correlated with imaging parameters. Analysis of variance or a mixed-effects model were used for groupwise comparisons. Results A total of 12 neonates (mean gestational age, 39 6/7 weeks ± 1/7 [SD]) were included and underwent ASO a mean of 6.9 days ± 3.4 after birth. When compared with baseline values, T-CEUS revealed a longer mean time-to-peak (right hemisphere, 4.3 seconds ± 2.1 vs 17 seconds ± 6.4 [P < .001]; left hemisphere, 4.0 seconds ± 2.3 vs 21 seconds ± 8.7 [P < .001]) and rise time (right hemisphere, 3.5 seconds ± 1.7 vs 11 seconds ± 5.1 [P = .002]; left hemisphere, 3.4 seconds ± 2.0 vs 22 seconds ± 7.8 [P = .004]) in both cerebral hemispheres during low-flow cardiopulmonary bypass and hypothermia (T4) for all neonates. Neonate age at surgery negatively correlated with T-CEUS parameters during ASO, as calculated with the area under the flow curve (AUC) during wash-in (R = -0.60, P = .020), washout (R = -0.82, P = .002), and both wash-in and washout (R = -0.79, P = .004). Mean AUC values were lower in neonates older than 7 days compared with younger neonates during wash-in ([87 arbitrary units au ± 77] × 102 vs [270 au ± 164] × 102, P = .049]), washout ([15 au ± 11] × 103 vs [65 au ± 38] × 103, P = .020]) and both wash-in and washout ([24 au ± 18] × 103 vs [92 au ± 53] × 103, P = .023). Conclusion Low-flow hypothermic conditions resulted in reduced cerebral perfusion, as measured with transfontanellar contrast-enhanced US, which inversely correlated with age at surgery. Clinical trial registration no. NCT03215628 © RSNA, 2022 Online supplemental material is available for this article.
CRIS-Team Scopus Importer:2022-07-01